The importance of valuing marine conservation area - Latiff, Norasilah; Mohammad Afandi, Syamsul Herman; Shuib, Ahmad (Institut Kajian Dasar Pertanian dan Makanan, Universiti Putra Malaysia, 2015)
Marine ecosystem has highest values especially towards quality of life and country economic growth. Basically, the function of marine ecosystem can be classified into three groups: economic (resorts, chalet and hotels), social (recreational activities) and environmental. Development of resorts, recreational activities, offshore and aquaculture activities are few of examples. The poor management, unplanned, and over exploitation can damage the marine ecosystem. This paper focus is to review the importance of valuing marine resources. Besides, this paper aims to review the useful method that can be applied to generate the values of marine resources by using economic valuation method and the validity of a method based on previous studies. Based on the previous studies, economic valuation classified into non-market stated preferences method and market based revealed preferences method. In each group they have provided several methods, i.e. Market price method, productivity method, hedonic pricing method, travel cost method, contingent valuation method, contingent choice method, benefit transfer method. Therefore, the value can be used as a conversion of a quantity, quality and the changes of price (monetary value). At the end of this paper, it can be used as a future references, especially in the scope of valuing of marine conservation area.